Immunohistochemical expression of p63, p53 in urinary bladder carcinoma - Ali Koyuncuer (Wolters Kluwer Medknow Publications, 2013)
Background: Urothelial carcinomas (UC) is of the most common cancers urinary bladder. Aim: The aim of the study is to assess the immunohistochemical staining differences between p63 and p53 according to the pathological stage and histological grade of the tumor in urinary bladder carcinomas. Materials and Methods: Totally 62 urinary bladder transurethral resection materials diagnosed with urothelial carcinoma in the pathology department of our hospital were included in the study. On pathological examination, cases were dichotomized as noninvasive and invasive, whereas noninvasive cases were dichotomized as low grade and high grade and invasive cases were dichotomized as pT1 and pT2. Subsequently, the cases were evaluated by means of p63 and p53 immunohistochemical staining. Statistical analyses were performed by SPSS program, and Chi-square and Fisher's exact tests. Results: When pTa was evaluated in terms of p63 immunoreactivity, no statistically significant difference was observed between LGPUC and HGPUC, noninvasive papillary UC, regarding staining percentages ( P > 0.05), whereas statistically significant relation was observed for pT1 and pT2 regarding p63 staining percentages ( P < 0.05). For pTa, no statistically significant relation was observed between LGPUC and HGPUC, noninvasive papillary UC, in terms of p53 staining percentages ( P > 0.05). However, highly significant relationship was observed for pT1 and pT2 in terms of p53 staining percentages ( P < 0.01). No significant relationship was observed between the staining percentages of p53 and p63 ( P > 0.05). Conclusion: The role of p53 and p63 immunoreactivities in the differential diagnosis and prognosis of urinary bladder carcinomas according to the pathological stage and histological grade of the tumor will be understood better with the increasing number of long term investigations performed with large series at a molecular level.